PENGARUH PENGGUNAAN GAWAI TERHADAP PERKEMBANGAN SOSIAL EMOSIONAL ANAK USIA 4-6 TAHUN - Elly Purwanti; Mashudah (LPPM STAI DARUSSALAM LAMPUNG, 2020)
The background of this research is that in this era it is familiar to us to see underage children already holding devices. Children born today are born as Native Digital Generations, namely children born in the digital era and interact with various digital devices. This phenomenon also occurred in RA Jami'atul Ikhwan Mataram Baru, an area of East Lampung district, where the RA students were more engaged and liked to watch videos. The aim of this research is to find out what kind of effect the use of gadgets in children aged 4-6 years old on the social emotional of students in RA Jami'atul Ikhwan Mataram Baru, East Lampung. This study uses a quantitative approach with research instruments in the form of questionnaires and analysis tools in the form of SPSS. From the table the regression results show a significance level of 0.11 which is greater than 0.05. This means that there is no significant effect of the use of gadgets on the social emotional of early childhood in RA Jami'atul Ikhwan Mataram Baru, East Lampung. It also shows that the use of devices affects the social emotional of early childhood by 20.7% and the other 79.3% is influenced by other variables outside the study. As for the impact of using the device as a whole, it has a moderate impact on the social emotional of early childhood, amounting to 18 people, high 6 and low 6 people.